A longitudinal study of HPV detection and cervical pathology in HIV infected women. Issue 4 (1st August 2000) - Cubie, H A; Seagar, A L; Beattie, G J; Monaghan, S; Williams, A R W
Abstract : Objective: To monitor the presence and persistence of high risk (HR) human papillomavirus (HPV) in cervical brushings from HIV infected women. Methods: Prospective observational cohort study of HIV infected women. Women were enrolled from the cohort of 164 HIV infected women who attend the colposcopy clinic at the Edinburgh Regional Infectious Diseases Unit. A single cervical brush scrape was obtained from 39 women and two or more samples from 63 women who attended regularly at approximately 6 monthly intervals. HPV typing was carried out using a commercial hybrid capture assay (HCA). Details of antiretroviral therapy, cytological assessment, and histological evaluation were made available and the interrelation with HR-HPV detection analysed. Results: Abnormal cervical cytology, particularly of low grade, was common in these HIV infected women. HR-HPV types were detected in 25% of the women with normal cytology, while over 80% of those with abnormal cytology of any grade were HR-HPV positive. Persistent HR-HPV, as defined by two or more consecutive HPV positive results, was common and found in 27/63 women from whom multiple samples were obtained. HR-HPV was detected at high levels whether or not patients were receiving antiretroviral therapy. Profound immunosuppression was not necessarily associated with progression of cervical disease and no cases of invasive cervical disease were seen. Conclusion: While mild dyskaryosis (low grade squamous intraepithelial lesion (LSIL)) and persistence of HR-HPV are common in HIV infected women in Edinburgh, regular cytological and colposcopic evaluation with appropriate intervention and treatment appears to limit the progression of cervical disease.